A Quantitative Study on the Influencing Factors of AI-Powered Elderly E-commerce Consumption - Shen, Sicong; Chang, Peng Kee; Mohd Nor, Nur Haniz (Innovative Applications of AI, 2025)
By 2035, my country's population aged 60 and over is projected to exceed 400 million, marking the beginning of a period of advanced aging. This trend is accompanied by the rapid development of new productivity, exemplified by Artificial Intelligence, creating new opportunities for silver e-commerce. E-commerce platforms not only improve shopping and payment efficiency for senior consumers but also become a crucial channel for unlocking their consumption potential and expanding the silver market. Based on the Technology Acceptance Model, this study constructs a theoretical model of how AI influences e-commerce consumption behavior among seniors. Data were collected through a questionnaire survey and empirically tested using structural equation modeling (SEM). The study focuses on the mechanisms by which internal and external variables, such as perceived usefulness, perceived ease of use, digital literacy, and social support, influence consumer intention. The study aims to provide empirical evidence and strategic recommendations for the AI-enabled silver economy, improving the quality of life of seniors, and promoting the development of "elderly-rich synergy."